Republic of Lithuania : 2010 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Lithuania. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Lithuania experienced a severe output decline. A large consolidation contained the deterioration in the fiscal deficit and safeguarded market financing. Further fiscal consolidation is needed to place deficits and debt on a sustainable path. Tackling the deficit in the social security system and expanding the revenue base will achieve adjustment in a sustainable, pro-growth, and equitable manner. A sustained recovery also hinges on the ability of the economy to rebalance toward tradables. The rising level of unemployment makes it imperative to advance with structural reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet